DOXOLOGI, TRADISI REFORMED DAN MIMBAR: KONSEP ALLAH TRITUNGGAL DALAM PEMIKIRAN JONATHAN EDWARDS SEBAGAI BAGIAN DARI TRADISI PELAYANAN MIMBAR REFORMED - Jimmy Pardede (STTRII, 2014)
Jonathan Edwards' brilliant conception that combines disposition and being, and God's absolute being with dynamicity, has challenged the most commonly accepted classical greek dualism between being and becoming, and absolute and dynamicity. This conception was found in his Trinitarian view of creation. God's disposition to repeat His eternal glory was seen as one of the unique characteristic in Edwards' treatment on both his doctrine of the Trinity, and also his doctrine of creation. But this unique combination on disposition and being is also perfectly applicable in seeing the nature of preaching, repentance, and the spirituality of a true Christian.?